ANALISIS PENGARUH JOB INSECURITY, KEPUASAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KEINGINAN BERPINDAH KARYAWAN (Studi pada Karyawan Outsourcing PT. POS Indonesia Cabang Kudus) - Alifian, Ima; Rahardjo, Mudji (Diponegoro Journal of Management, 2016)
This study aims to analyze the influence of the job insecurity, job satisfaction, and commitment organization on intention to quit. This study used cencus method with 37 respondents as employee of outsourcing in the PT POS Indonesia (Persero) Branch Kudus.Technique test of the data used in this study include validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination test (R2) using SPSS application. The results showed that the content of the job insecurity have a positive and significant impact on intention to quit, while the job satisfaction and commitment organization have a negative and significant impact on intention to quit. Through the F test showed that the variable independents have simultaneous effect on intention to quit with significant result. Figures adjusted R square of 0,541 indicates that 54,1 percent the variations of intention to quit can be explained by variable used in the regression equation. While the rest of 45,9 percent is explained by another variables not included in this study.